ANALISIS PENGARUH BRAND AWARENESS, ATRIBUT PRODUK, DAN IKLAN TERHADAP MINAT BELI PRODUK KOSMETIK ORIFLAME DI KOTA SURAKARTA - Widiastuti, Erni (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2020)
The objectives of this study were to determine: (1) the influence of Brand Awareness on the purchase intention of Oriflame cosmetic products in Surakarta, (2) the effect of product attributes on the buying interest in Oriflamecosmetic products in Surakarta, (3) the effect of advertising on the buying interest in cosmetic products. Oriflame Surakarta, and (4) the influence of brand awareness, product attributes, and advertisements on buying interest in Oriflamecosmetic products in Surakarta. While the hypotheses in this study are: (1) Brand Awareness variable has a significant effect on buying interest in Oriflame cosmetic products in Surakarta City (2) Product attribute variables have a significant effect on buying interest in Oriflame cosmetic products in Surakarta (3) Advertising variables have a significant effect on interest. buy Oriflame cosmetic products in Surakarta City (4) Variables Brand Awareness, Product Attributes, and Advertising simultaneously have a significant effect on buying interest in Oriflame cosmetic products in Surakarta. The research was conducted in the city of Surakarta. Based on the calculation results, the number of samples used was around 96.04 respondents or rounded to 97 respondents, using accidental random sampling technique. The data collection technique used was a questionnaire method, documentation and literature study. The data analysis techniques in this study were the Instrument Test, Multiple Linear Regression Analysis, t test, F test and the coefficient of determination. From the Multiple Linear Regression Results, the Multiple Linear Regression Equation is obtained as follows: Y = -7.452 + 0.835 X1 + 0.587X2 + 0.310 X3 + e. Based on the research results, it can be concluded that: (1) Brand Awareness has a significant positive effect on buying interest in Oriflame cosmetic products in Surakarta. (2) Product attributes have a significant positive effect on buying interest in Oriflame cosmetic products in Surakarta. (3) Advertising has a significant positive effect on buying interest in Oriflame cosmetic products in Surakarta. (4) Brand Awareness, Product Attributes, and advertisement simultaneously have a significant positive effect on buying interest in Oriflame cosmetic products in Surakarta.